2019
DOI: 10.2217/pgs-2019-0004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic Testing in Primary Care Practice: Opinions of Physicians, Pharmacists and Patients

Abstract: Aim: Although health authorities have set pharmacogenetic (PGx) markers on labels of hundreds of drugs, the use of PGx in clinical care remains infrequent. The adoption of PGx will depend on the opinions of physicians, pharmacists and patients. Materials & methods: Qualitative focus group interviews were performed with 23 physicians, 11 pharmacists and 30 patients. Results: Majority of the participants showed enthusiasm toward the implementation of PGx in clinics. Lack of knowledge on PGx, roles of healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
79
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 47 publications
(57 reference statements)
3
79
0
5
Order By: Relevance
“…These included requests for future results on drugs not yet included in the study (psychiatric medications), as well as interest in whether their PGx results impacted other drugs that were not specifically referenced on their result report (other statins, or other blood thinners). Other studies have also demonstrated that participants with exposure to PGx results have a strong receptiveness toward the use of pharmacogenomics and desire to see it used more routinely [3,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These included requests for future results on drugs not yet included in the study (psychiatric medications), as well as interest in whether their PGx results impacted other drugs that were not specifically referenced on their result report (other statins, or other blood thinners). Other studies have also demonstrated that participants with exposure to PGx results have a strong receptiveness toward the use of pharmacogenomics and desire to see it used more routinely [3,[14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Most participants requesting genetic counseling (54%) were seeking general assistance with understanding their PGx result reports, often alluding to uncertainty regarding whether they should or should not take a given medication in the future based on their results. The expectation for PGx test results to have the potential to inform physician prescribing decisions in a way that maximizes drug efficacy while limiting adverse reactions has been captured in several other studies, including studies of participants who have received PGx results [2,3,[14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 A number of barriers have been identified, in cluding the lack of uptake in clinical guidelines. 8 Several institutions, often at academic medical centers, have overcome these barriers and clinical implementations are underway. [9][10][11] These institutions contribute to expanding ev idence supporting clinical utility of pharmacogenetics and provide lessons learned, which can facilitate additional clin ical implementations.…”
mentioning
confidence: 99%